Metal-free trifluoroethylation of activated alkenes: rapid access to construct fluorinated 3, 3-disubstituted 2-oxindoles. Issue 44 (4th November 2015) - Mai, Wen-Peng; Sun, Bin; Qian, Guan-Sheng; Yuan, Jin-Wei; Mao, Pu; Yang, Liang-Ru; Xiao, Yong-Mei
Abstract: A novel and mild fluorination/cyclization reaction of activated alkenes under metal-free conditions has been developed. Fluorinated radicals were produced from halogenated hydrocarbons by simple rongalit, meanwhile, no metal and extra base are needed. This method provides a general and rapid route to construct fluorinated 2-oxindoles in aqueous solution. Graphical abstract: